Government Policy in Health Services: Kebijakan Pemerintah dalam Pelayanan Kesehatan - Elungan, Anjely N. F.; Tjenreng, Muhammad Baharuddin Zubakhrum (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Government policies in health services play an important role in ensuring access and quality of health services for all levels of society. This policy covers various aspects, from the provision of health facilities, financing, to the regulation of health workers and supervision of the health system. The government is responsible for designing and implementing policies that can reduce inequalities in access to health, increase the efficiency of the health system, and ensure quality and affordable services for the community. In this context, health policies must be adaptive to the dynamics of social, economic and technological developments. This research aims to analyze various policies that have been implemented by the government in the health sector, as well as the challenges and opportunities faced in their implementation. By understanding this policy, it is hoped that more effective solutions can be found to improve the quality of health services in the future.